Chitosan as a coating material in enhancing the controlled release behaviour of zinc hydroxide nitrate-sodium dodecylsulphate-bispyribac nanocomposite - Norhayati Hashim (Tanjung Malim, 2021)
Chitosan as a coating material in enhancing the controlled release behaviour of zinc hydroxide nitrate-sodium dodecylsulphate-bispyribac nanocomposite by Norhayati Hashim